Islamic Innovation in Malaysian Public Service - Ilhaamie Abdul Ghani Azmi; Junaidah Hashim (Kajian Malaysia, 2022)
Presently, there are few articles that discuss on Islamic innovation. Henceforth, this article will try to elaborate on this matter about the concepts, principles, purpose, factors of innovation in Islam, famous Islamic scholars for innovation and modern Muslim innovators. In addition, this article will also elaborate the concepts of Islamic innovation which are tajdid, islah and ijtihad in Malaysian public service context by using library research method i.e., through examining online reports, document review from previous research, and Quran and Hadith verses. This understanding is pertinent as Malaysia is an Islamic country whereby Islam is the official religion. The public sector should be spearheading innovation in the country to elevate the country to greater heights.